Technology-Intense Service Offerings in the Light of Economic Complexity: Establishing a Holistic Service Ecosystem - Veronika Belousova; Nikolay Chichkanov; Grigoriy Gashnikov; Zhaklin Krayushkina; Thomas Thurner (Foresight and STI Governance)
Crisis situations, like the COVID-19 pandemic, have historically been identified as times of enhanced innovation and entrepreneurial activities. Innovation actors are required to respond quickly to a new situation bearing in mind the effects of actions across their network of partners and competitors as well as rising economic complexity. Indeed, first indications suggest that this pandemic is no different and has facilitated the use of digital technologies. In order to assess these developments, this paper studies new service offerings based on digital technologies using the example of three major Russian banks. We found that banks have now developed into technology platforms that use their experience to engage in areas like education, advanced robotics, and health care. Technologies developed by partner organizations, such as the integration of blockchain solutions, have spread rapidly.  Thereby, banks have obtained a strategic advantage for launching innovations in the financial industry, including technology and knowledge transfers from other industries.